Procedural forms of use of special knowledge at investigation on ecological offenses by the legislation of the Republic of Kazakhstan (Journal of actual problems of jurisprudence, 2018)
In this article authors open tendencies of development of criminally procedural legislation in Kazakhstan concerning institute of special knowledge. Authors note that all procedure of attraction the special knowledge, or special scientific knowledge has a legal regulation. The legislator defines subjects, purposes and problems of special knowledge realization and the rights and duties of the subjects involved in this process. In scientific literature regarding whom it is necessary to rank as dispute subjects, there are no discussions, but authors emphasize that there were offers from the party of protection during the Soviet period to grant them the right to appoint examination or to address to the expert. This offer was proved by the justice purposes, such as a possibility of achievement the truth, realization of the principle of competitiveness, etc.. The legislator has considered these offers. In article 117 of Code of Criminal Procedure of the RK the right to address to experts is granted to the parties, they conduct researches, make out them according to requirements of Art. 117 and results of their research are accepted as the proof on an equal basis with other types of proofs. Furthermore, authors pay special attention to questions of use of judicial examination at proof of circumstances of ecological offense. The maintenance of the concepts “subject”, “tasks”, “questions” of judicial environmental assessment is analyzed, classification of the subjects authorized according to the criminal procedure legislation to appoint judicial examination, to prepare the materials directed to the expert is given. To conclude the article authors on the basis of the analysis of court practice note that in Kazakhstan there is a formation of a class of judicial environmental assessment and in practice there are problems at purpose of judicial examination, granting materials to the expert and other questions which should be resolved. Key words: Republic of Kazakhstan, criminal procedure, expert consultation, examination, identification, diagnostics, expert, specialist, report, conclusions.